Measuring Performance in Marketing - Thomas, Michael (Ekonomika, 2005)
This article draws attention to the importance of the capabilities of the new member states of the European Union and public accountability under increased competitive pressure. Among the topics dicussed in the paper are the role of global marketing players and the concept of measuring marketing, in which three levels of measurement are distinguished. A model is presented in which marketing measures are applied toward measuring and creating value, the main elements of which are brand building and brand development.